Genetic Variability Analysis of Hot Pepper (Capsicum Annuum.L) Landraces at Haramaya University, Eastern Ethiopia - Abdurazak Sufiyan, (Indian Journal of Advanced Botany (IJAB), 2025)
Hot pepper is a globally important spice utilized for food flavoring, enhancement, and coloring, with a growing demand over time. In the 2023/2024 cropping season, this study aimed to assess the genetic variability among 19 landrace genotypes and one improved hot pepper genotype under semiirrigation conditions. Twelve quantitative parameters were evaluated using a randomized complete block design with three replications. Analysis of variance revealed highly significant differences (P ≤ 0.01) for all traits except days to harvest and fruit weight, which were non-significant. Coefficients of variation ranged from 2.92 for days to fifty percent flowering to 31.47 for number of fruits per plant, indicating substantial variability among accessions. Fruit length varied from 4.5cm (accession 229694) to 11.17cm (accession 229699), while fruit width ranged from 8.33cm to 31.4cm, and fruit weight from 11.25g to 24.88g. Accession 229697 exhibited the highest fruit number per plant (42.67), while M/fana showed the lowest (12.67), with a mean value of 23.64. Fruit yield per plot ranged from 0.26kg/plot (accession 229696) to 0.91kg/plot (accession 28337), with approximately 40% of genotypes surpassing the population mean (0.5935kg/plot). High phenotypic and genotypic coefficients of variation, along with high genetic advance and heritability, were observed for yield per plot, number of fruits per plant, and fruit width, suggesting potential for improvement through selection. Based on the study results, accession 28337 for yield per plot, accession 229697 for fruit number per plant, and accession 229695 for fruit width are recommended for future selection.